PWE-223 Gastroenterology investigations for iron deficiency anaemia (IDA) in patients with acute coronary syndrome awaiting cardiac interventions. How good are our cardiology colleagues?. (28th May 2012) - Rahman, Z U; Mansoor, M; Hamid, T; Latif, O; Campbell, S
Abstract : Introduction: Anaemia is associated with increased risk of morbidity and mortality in patients with ischaemic heart disease (IHD) and heart failure. Incidental anaemia in patients awaiting coronary interventions is common particularly in our elderly populations. Currently there are no clear guidelines how to investigate these patients. The elderly patients have a higher RR of having occult GI malignancy and endoscopy is the gold standard to identify early disease. Majority of the physicians refer patients with anaemia to gastroenterologists routinely to exclude GI pathology. Endoscopic investigations are however not without complications and generally contraindicated during acute coronary syndrome. Methods: This is a retrospective analysis of patients with anaemia admitted with acute coronary syndrome to our hospital. Information was collected from patient records and endoscopy reporting database over a period of 2 years (January 2009–December 2010). We analysed all the investigations, outcomes/diagnosis of these patients. The data were analysed by Standard statistical methods. Results: A total of 230 patients were identified by the coding department with anaemia and IHD who were admitted over a period of 24 months. However, only 61 (26.5%) patients were investigated for anaemia. The mean age was 70±19 years with 77% (47/61) were more than 60 years of age. Serum Ferritin was checked in only 50% (31/61) of these patients before referral, out of which 71% (22/31) patients had low levels. Coeliac serology was done in only 5% (3/61) patients, which was normal. 75.5% (46/61) of the referred patients underwent Oesophagogastroduodenoscopy (OGD), 13.04% (6/46) had non-erosive gastritis and 8.69% had peptic ulcer. Others had angiodysplasia, gastric erosions, gastric polyps and hiatus hernia in 4.3% each. OGD was normal in the rest; none had cancer or active bleeding. Colonoscopy was performed in 54.09% (33/61) patients and CT colonogram in 5%. Colorectal cancer was found 8.33% (3/36) patients, benign polyps in 5.55% and diverticulosis in 22%. Conclusion: A large number (73%; 169/230) of the anaemic patients with IHD were not referred to rule out gastrointestinal cause of anaemia. Coeliac serology is poorly checked by the Cardiologists. The prevalence of colorectal cancer was high that is, 8.33% in the small proportion of those referred. We suggest appropriate screening and thorough evaluation of anaemia in cardiology setting. This can be done by following British Society of Gastroenterology guidelines for investigation of iron deficiency anaemia. Education of colleagues would be of paramount importance in optimising appropriate referral practice. Competing interests: None declared.